Intensity and regimes changing of hydrodynamic cavitation considering temperature effects. (1st March 2022) - Ge, Mingming; Zhang, Guangjian; Petkovšek, Martin; Long, Kunpeng; Coutier-Delgosha, Olivier
Abstract: Venturi-type cavitation reactors still appear as the most promising candidates for industrial-scale production due to their cheapness and ease of construction, scaling, and replicability. The effects of temperature on hydrodynamic cavitating flows in a Venturi section are investigated to find the optimum reacting conditions enhancing cavitating treatment intensity. The flow conditions are varied with 4 different flow rates and a wide range of temperatures between 28 ℃ to 63 ℃. Results show that both the cavitation length and the transition between sheet and cloud cavitation regimes are influenced by a combination of the pressure drop (indicated by the cavitation number σ ), the inertial/viscous effects (controlled by the Reynolds number Re ), and the thermal effect (indicated by the thermodynamic parameter Σ ). As the temperature is elevated, both the cavitation length and thickness increase first, and then decrease. The cavitation intensity peaks at a transition temperature of 58 ℃. With the increase of cavitation length and thickness, the regimes tend to switch earlier from the attached sheet cavity to periodical cloud shedding, and the shedding frequency decreases accordingly. When the temperature is progressively increased, the changing of cavitating flow structures is illustrated through Proper Order Decomposition analysis. This study allows us to understand the instability, size evolution, shedding regime transition of partial cavities considering thermodynamic effects. Recommendations are provided to beer-brewing, biodiesel production, or water treatment industries that working under a 55 ℃ to 60 ℃ temperature range will attain the highest cavitation intensity. Highlights: Temperature, Reynolds number and cavitation number affect HC performance. The increase–decrease trend of cavity length is confirmed and analyzed. POD method is developed to distinguish sheet cavitation and cloud cavitation. Cavitation intensity peaks and shedding regimes transition happens at 58 °C.